2018
DOI: 10.1158/0008-5472.can-17-3964
|View full text |Cite
|
Sign up to set email alerts
|

Canonical Wnt Signaling Remodels Lipid Metabolism in Zebrafish Hepatocytes following Ras Oncogenic Insult

Abstract: There is limited understanding of the effects of major oncogenic pathways and their combinatorial actions on lipid composition and transformation during hepatic tumorigenesis. Here, we report a negative correlation of Wnt/Myc activity with steatosis in human hepatocellular carcinoma (HCC) and perform functional studies using three conditional transgenic zebrafish models. Double-transgenic zebrafish larvae conditionally expressing human and zebrafish or murine together with in hepatocytes led to severe hepatome… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
66
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 52 publications
(67 citation statements)
references
References 44 publications
1
66
0
Order By: Relevance
“…Myl7 promoter has also been extensively employed to drive gene expression in atrial and ventricular myocardium in zebrafish hearts at all stages (Thisse et al, 2004; Hsiao et al, 2003). We generated myl7 promotor-driven and dosage-induced (Tet-On system) transgenic cassettes (Yao et al, 2018) for delicate regulations of tnnt2a expression (Fig. 2A,B).…”
Section: Resultsmentioning
confidence: 99%
“…Myl7 promoter has also been extensively employed to drive gene expression in atrial and ventricular myocardium in zebrafish hearts at all stages (Thisse et al, 2004; Hsiao et al, 2003). We generated myl7 promotor-driven and dosage-induced (Tet-On system) transgenic cassettes (Yao et al, 2018) for delicate regulations of tnnt2a expression (Fig. 2A,B).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, linoleic acid was shown to induce breast cancer cell migration through plasminogen activator inhibitor-1 (PAI-1) and SMAD4 [63]. In a recent study, Yao et al found that canonical Wnt signaling through MYC promotes the conversion of triacylglycerol to phospholipid and increases unsaturated fatty acyl groups in phospholipids [64]. This lipid metabolism remodeling is extensively used by cancer cells as unsaturated fatty acids are crucial for the cell membrane maintenance, energy storage and signaling [65].…”
Section: Wnt Signaling In Cancer Lipogenesismentioning
confidence: 99%
“…Wnt signaling is involved in the stability of Ras through regulation of glycogen synthase kinas 3β-mediated Ras phosphorylation [56]. In hepatocellular carcinoma, Wnt signaling modulates lipid homeostasis in a Ras-dependent manner [57]. In this study, we found that Ras activity modulates the expression level of NUDT7 in an opposite manner, and decreased levels of NUDT7 deregulate lipid homeostasis by the upregulation of Wnt signaling.…”
Section: Discussionmentioning
confidence: 59%